2014
DOI: 10.1136/jramc-2014-000259
|View full text |Cite
|
Sign up to set email alerts
|

Screening for latent tuberculosis and gastrointestinal parasite infections in Gurkha recruits: research driving policy change

Abstract: Nepalese Gurkha soldiers are recruited from a country endemic for a number of infectious diseases, including tuberculosis and gastrointestinal parasites. This article describes a prospective cohort study which investigated screening strategies for these infections among Gurkha recruits arriving in the UK to begin basic training. Several recommendations were made as a result of the study which were supported for early implementation and subsequently fully adopted. Military screening and treatment policies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In light of the findings presented in this study the UK Ministry of Defence has altered its policy for LTBI screening in Gurkha recruits to the use of a single T-SPOT.TB IGRA [53] . These findings are important because they have implications for LTBI diagnostic strategies in populations of migrants arriving in countries of low TB incidence from areas of high TB incidence.…”
Section: Discussionmentioning
confidence: 96%
“…In light of the findings presented in this study the UK Ministry of Defence has altered its policy for LTBI screening in Gurkha recruits to the use of a single T-SPOT.TB IGRA [53] . These findings are important because they have implications for LTBI diagnostic strategies in populations of migrants arriving in countries of low TB incidence from areas of high TB incidence.…”
Section: Discussionmentioning
confidence: 96%
“…With the exception of the early work by O’Shea et al in this population [ 11 , 12 ], there are limited recent published data on GIP infection in otherwise healthy or asymptomatic migrants to the UK. A large study in 4,000 schoolchildren conducted in the 1970s found a helminth prevalence of 30–40% in those migrating from Pakistan or India, but no participants were recorded as coming from Nepal [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK a screening programme has been in place since 2012 for personnel recruited from Nepal for the Gurkha regiments of the United Kingdom Armed Forces. Historical data had suggested high rates of helminth infection in this population [10], supported by more recent work showing a GIP prevalence of 21.7% [11,12]. In this retrospective study, we review the data from 9 years (up to 2020) of screening 2,263 members of this large, homogenous, well controlled population of healthy and economically active migrants from a GIP endemic location, namely Nepal.…”
Section: Introductionmentioning
confidence: 87%